Online learning challenges during pandemic COVID-19 in Malaysian Higher Learning Institution - Nur Salina, Ismail; Nor Mazlina, Abu Bakar@Harun; Sharifah Wajihah Wafa, Syed Saadun Tarek Wafa (2020)
Since the announcement of the movement control order (MCO) to help curb the spread of COVID-19 virus, education institutions across the nation have taken great measures to ensure that their students can continue learning through digital means. Hence, academicians and students have to start setting their mind that they have to adapt new learning processes that do not allow physical meetings. This has raised concerns on how students are to cope with this new online learning environment since they come from different socioeconomic backgrounds. Therefore, the aim of this study is to identify the challenges faced by university students when implementing online learning during pandemic COVID-19. A preliminary online study is conducted among 542 students in Universiti Sultan Zainal Abidin Malaysia (UniSZA) to investigate the challenges and problems they may face adapting with the new “norm”. The findings indicated that the majority of the students are not ready for online learning as the main challenge faced is low internet access to enable them for online learning. The findings from this study have benefitted the university management in making prompt and effective decisions concerning the implementation of remote learning during the pandemic. In order to get the full benefit of online learning, a concerted effort is needed from many as to provide this structure and go beyond replicating a physical class/lecture.